ALTERNATIF MENINGKATKAN PEMAHAMAN SISWA MATERI KETENAGAKERJAAN MASA PANDEMI COVID-19 MELALUI MODEL SESI INTEGRASI BERBASIS CLASSROOM, - Ruminten Supadmi (Universitas Sultan Ageng Tirtayasa, 2022)
The classroom-based “Integration Session” model is used in this study as an alternative learning for the Covid-19 pandemic disaster preparedness. The type of research is Classroom Action Research with 2 cycles. Two meetings in each cycle. Research subjects, students of class XI IPS 2 SMA Negeri 1 Rangkasbitung FY 2021/2022. Tests and non-tests were used as instruments. Data collection techniques through 1). Documentation: Google Classroom application, Google Form, Google Documentation, 2) Essays and multiple choice tests, 3) To find out student responses to the application of the classroom-based “Integration Session” model, a questionnaire was used. Data reduction, data presentation, and drawing conclusions were used as analytical steps. Before applying the